Effects of Raschig ring packing patterns on pressure drop, heat transfer, methane conversion, and coke deposition on a semi-pilot-scale packed bed reformer - Chutichairattanaphum, Nattaporn (Array, 2019)
The effects of Raschig ring packing patterns on the efficiency of dry methane reforming reactions were investigated using computational fluid dynamics (CFD). The present study aims to understand the behavior of fluid flow in packed bed reactors, especially under low reactor-to-ring ratios between 4 and 8. Three packing patterns were studied: vertical staggered (VS), chessboard staggered (CS), and reciprocal staggered (RS). It was determined that packing pattern notably affected pressure drop across the reactor length. The VS pattern produced the lowest pressure drop of 223 mPa, while the CS and RS patterns produced pressure drops of 228 mPa and 308 mPa, respectively. The values of methane conversion can be increased by ca. 2 % by selecting a more suitable packing pattern (i.e., 76 % for the VS pattern and 74 % for the CS and RS patterns).